2021
DOI: 10.3390/s21113580
|View full text |Cite
|
Sign up to set email alerts
|

Assembly Assistance System with Decision Trees and Ensemble Learning

Abstract: This paper presents different prediction methods based on decision tree and ensemble learning to suggest possible next assembly steps. The predictor is designed to be a component of a sensor-based assembly assistance system whose goal is to provide support via adaptive instructions, considering the assembly progress and, in the future, the estimation of user emotions during training. The assembly assistance station supports inexperienced manufacturing workers, but it can be useful in assisting experienced work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
(77 reference statements)
1
8
0
Order By: Relevance
“…The Markovian-based predictors suffer from not having all the scenarios available in the training data, resulting in a lower prediction rate but higher accuracy. This was also observed in a previous study [37], where the feature importance metrics could be observed from the algorithms. The main feature used for prediction was the state of the tablet, with a representation of over 98% of the splits inside the predictor, at least for the GBDT presented in the study.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The Markovian-based predictors suffer from not having all the scenarios available in the training data, resulting in a lower prediction rate but higher accuracy. This was also observed in a previous study [37], where the feature importance metrics could be observed from the algorithms. The main feature used for prediction was the state of the tablet, with a representation of over 98% of the splits inside the predictor, at least for the GBDT presented in the study.…”
Section: Resultssupporting
confidence: 84%
“…Another part of the heuristic obtaining a considerable score is the ordering of the items in the queue as when no Markov score is present, the last item will be the following child, with the lowest state score described in the methodology used in [28]. Analyzing Figures 9 and 10, similar results to [37] were observed, namely, that for the algorithm, it is easier to learn the behavior of the manufacturing workers, which, based on their experience, are more conservative in their assembly patterns. The increase of 14% in the prediction power can also be attributed to the narrower range of unique assemblies available in the manufacturing dataset compared to the students' dataset, where several unique assemblies were met; whenever the algorithm predicted equal chances for both of them, the first one added in the queue would be picked.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Some studies evaluated worker 's performance of textile company by using ML and ensemble learning algorithm, such as study as Saad 2020. [23] which applied different Machine learning algorithms including, decision tree and bagging algorithm to achieve the highest accuracy. The CHAID model produced high-level specificity and sensitivity.…”
Section: Related Workmentioning
confidence: 99%